Temperature-growth divergence in white spruce forests of Old Crow Flats, Yukon Territory, and adjacent regions of northwestern North America - Porter, Trevor J.; Pisaric, Michael F.J. (Global Change Biology, 2011)
This is the accepted manuscript of an article published by Wiley. We present a new 23-site network of white spruce ring-width chronologies near boreal treeline in Old Crow Flats, Yukon Territory, Canada. Most chronologies span the last 300 years, and some reach the mid-16th century. The chronologies exhibit coherent growth patterns before the 1930s. However, since the 1930s they diverge in trend and exhibit one of two contrasting, but well-replicated patterns we call Group 1 and Group 2. Over the instrumental period (1930-2007) Group 1 sites were inversely correlated with previous-year July temperatures while Group 2 sites were positively correlated with growth-year June temperatures. At the broader northwestern North America (NWNA) scale, we find that the Group 1 and Group 2 patterns are common to a number of white spruce chronologies, which we call NWNA 1 and NWNA 2 chronologies. The NWNA 1 and NWNA 2 chronologies also share a single coherent growth pattern prior to their divergence (~1950s). Comparison of the NWNA 1/NWNA 2 chronologies against gridded 20th-century temperatures for NWNA and reconstructed Northern Hemisphere summer temperatures (A.D. 1300-2000) indicates that all sites responded positively to temperature prior to the mid-20th century (at least back to A.D. 1300), but that some changed to a negative response (NWNA 1) while others maintained a positive response (NWNA 2). The spatial extent of divergence implies a large-scale forcing. As the divergence appears to be restricted to the 20th century, we suggest the temperature response shift represents a moisture stress caused by an anomalously warm, dry 20th-century climate in NWNA, as indicated by paleoclimatic records. However, because some sites do not diverge, and are located within a few kilometres of divergent sites, we speculate that site-level factors have been important in determining the susceptibility of sites to the large-scale drivers of divergence. This research was supported by a NSERC Discovery Grant, NSERC Northern Supplement and Government of Canada IPY grant to M. Pisaric; and a NSERC Graduate Scholarship and Northern Scientific Training Program grant to T. Porter.